E-Commerce Applications In Helping Selling Handphone Products In Ficho Mobile Store - Alfatah, Dhika (Jurnal Media Computer Science, 2023)
Driven by technological advances and computerization to improve work efficiency through sales on the internet An e-commerce is familiar to consumers, many online stores are frequently visited by consumers. ficho cellular. Adding consumers who will transact at the ficho cellular store. The data collection method used in conducting this research is through primary data (interviews, observations) and secondary data (documents). This research was carried out on July 2 to August 19, 2021. From the results of research and testing that has been done, the design of an E-Commerce application in Helping Sales of Mobile Products at the Ficho Cellular Store can be done by applying php mysql and can be well integrated